Key Technology in Detecting and Eliminating Isomerism Fibre in Cotton - Li Yujun; Liang Kun; Bai HuaYu (2007 8th International Conference on Electronic Measurement and Instruments, 2007)
Framework and working principle of detecting and eliminating isomerism fibre in cotton system online is introduced and several key technologies involved in its design are analyzed. Experiment studies are implemented and advances solved scheme. In the technologic methods flow of cleaning and rippling the cotton, cotton has been loosed enough and impurity is removed. Then a linear CCD (charge coupled device) camera is used to capture the image of cotton and foreign fibre, from the camera. The images are sent to the industry control computer through a high-speed frame grabber acquires digital card and operated in computer. HSI (Hue, saturation, Intensity) color model threshold method and binarization algorithm are used to distinguish cotton with isomerism fibre. When finding the foreign fibre, the computer will send out an instrument to drive the corresponding position gas-act electromagnetism valve to act and using high-pressure gas to jet it out to the trash box. Through a series of experiments and locale debug analysis, a sample machine system is established. Through testing it can reach the need of control and exact distinguish the cotton and isomerism fibre in real time and eliminate it.